The correct name of Clibanornis rubiginosus watkinsi (Hellmayr, 1912 (Passeriformes: Furnariidae) - Costa, Thiago V. V. (Zootaxa, 2017)
The “Watkins’s” Ruddy Foliage-gleaner was described as Automolus watkinsi by Carl Eduard Hellmayr (1912), based on one specimen collected two years earlier in Yahuarmayo, Marcapata, Peru. It is known to occur in the Andean foothills from northern Peru south to northern Bolivia and in extreme western Amazonian Brazil (Remsen 2003). This species has recently been subsumed in the genus Clibanornis, as some studies have shown that it is more closely related to that genus and to Hylocryptus than it is to the other Automolus (Derryberry et al. 2011; Claramunt et al. 2013), affinities that had in part already been suggested due to their similarities in morphology (Chapman 1919). It is currently considered either subspecies of C. rubiginosus (Remsen 2003; del Hoyo et al. 2016; Remsen et al. 2017) or a distinct species (e.g. Piacentini et al. 2015).